A Bioanalytical Method for Eliglustat Quantification in Rat Plasma. (16th May 2019) - Reddy, Venkata Krishna; Swamy, Narayana; Rathod, Rajeswari; Sengupta, Pinaki
Abstract: A simple and sensitive bioanalytical HPLC–UV method has been developed and validated for quantification of eliglustat in rat plasma. The liquid–liquid extraction method was found to be more efficient compared to protein precipitation technique. Chromatographic separation of eliglustat was achieved using Kromasil C18 column with a mobile phase consisting of a mixture of methanol and ammonium acetate (pH 3.2) in a ratio of 60:40. Detection wavelength was set at 282 nm. The developed method was specific, accurate, precise with good recovery and stability profile. The calibration curve constructed over a range of 0.3–10 μg/mL was linear ( R 2 > 0.997). Accuracy in intra and inter-day assay were found to be 96.27–107.35% and 96.80–106.57%, respectively. The corresponding precision (%CV) values were within 4.31–10.90% and 4.82–9.97%, respectively. Till date, no method is available for bioanalysis of eliglustat in any type of biological matrix. This is the first time to report a bioanalytical method for this molecule. The developed bioanalytical method was applied to quantitate eliglustat in the plasma samples of a single dose oral pharmacokinetic study in Sprague Dawley rat.